2021
DOI: 10.1080/21655979.2021.1955580
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the serum miR-455-5p expression in patients with neonatal sepsis

Abstract: Sepsis is a systemic inflammatory response caused by infection and is a major cause of neonatal death. This study explored the miR-455-5p in neonatal sepsis, and further investigated the diagnostic and prognostic value of miR-455-5p in neonatal sepsis (NS). The levels of serum miR-455-5p in 88 healthy controls and 90 NS patients were examined by quantitative real-time polymerase chain reaction (qRT-PCR). Pearson correlation coefficient was used to evaluate the correlation between miR-455-5p and clinical featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Both hsa-miR-200b and hsa-miR-455 were found upregulated in pneumonia [66]. hsa-miR-455-5p was overexpressed in patients with neonatal sepsis compared to healthy controls and highly expressed miR-455-5p was associated with poor prognosis [67]. miR-455-5p was upregulated in rabies virus infection in vitro , decreased SOCS3 expression and increased STAT3 activity resulting in enhanced viral replication and the production of interleukin-6 (IL-6) [68].…”
Section: Discussionmentioning
confidence: 99%
“…Both hsa-miR-200b and hsa-miR-455 were found upregulated in pneumonia [66]. hsa-miR-455-5p was overexpressed in patients with neonatal sepsis compared to healthy controls and highly expressed miR-455-5p was associated with poor prognosis [67]. miR-455-5p was upregulated in rabies virus infection in vitro , decreased SOCS3 expression and increased STAT3 activity resulting in enhanced viral replication and the production of interleukin-6 (IL-6) [68].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-455-5p upregulation influences retinol absorption in a lung hypoplasia model by regulating STRA6 [ 47 ]. Moreover, miR-455-5p is considered to be a diagnostic and prognostic marker for neonatal sepsis [ 20 ]. A previous study has indicated that rno-miR-455-5p contributes to the proliferation of ESCs that are treated with TGF-β for establishing an IUA cell model [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-455-5p has attracted increasing attention and has been reported to participate in multiple disorders. For example, miR-455-5p upregulation is related to the poor prognosis of patients with neonatal sepsis [ 20 ]. Moreover, miR-455-5p inhibits the proliferation and migration of vascular smooth muscle cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%